THE DIVISION OF INHERITANCE OF ADOPTED CHILDREN IN THE INDIGENOUS PEOPLE OF KAMPUNG NAGA ASSOCIATED WITH ISLAMIC LAW - Bambang Daru Nugroho; Hazar Kusmayanti; Dede Mulyanto (Jurnal Bina Mulia Hukum, 2022)
Adoption of a child according to customary law is an act of taking another person's child into his own family in such a way that there is a kinship relationship that is the same as between parents and their own biological children. This research was conducted in Kampung Naga, Tasikmalaya Regency, because the majority of the population adheres to Islam but in all aspects of life including the distribution of inheritance still uses customary law rules. The purpose of this study is to examine the position of the inheritance rights of adopted children based on laws and regulations and the practice of inheritance distribution to adopted children. The research method uses normative juridical which is a juridical analytical research specification which will be processed in a qualitative juridical manner. The position of the adopted child's inheritance, if a court decision is requested, is carried out, a court ruling that will provide legal certainty to the adoptive parents and adopted child as strong evidence that it is true that there has been an adoption of a child. The two systems of adopting children are carried out not explicitly and not in cash, including those carried out in the Kampung Naga Community, Tasikmalaya Regency.